Incidence and trends of limb amputation in first nations and general population in Saskatchewan, 2006-2019. - Samuel Kwaku Essien; Gary Linassi; Margaret Larocque; Audrey Zucker-Levin (PLoS ONE)
Background There is conflicting evidence whether limb amputation (LA) disproportionately affects indigenous populations. To better understand this disparity, we compared the LA incidence rate between First Nations persons registered under the Indian Act of Canada (RI) and the general population (GP) in Saskatchewan. Methods We used Saskatchewan's retrospective administrative data containing hospital discharge LA cases, demographic characteristics (age and sex), and residents population reported in the database stratified by RI and GP from 2006-2019. The LA cases for each stratified group were first disaggregated into three broad categories: overall LA (all reported LA), primary LA (first reported LA), and subsequent LA (revision or contralateral LA), with each category further split into the level of amputation defined as major amputation (through/above the ankle/wrist joint) and minor amputation (below the ankle/wrist joint). LA rates were calculated using LA cases as the numerator and resident population as the denominator. Joinpoint and negative binomial regressions were performed to explore the trends further. Results Overall, there were 1347 RI and 4520 GP LA cases reported in Saskatchewan from 2006-2019. Primary LA made up approximately 64.5% (869) of RI and 74.5% (3369) of GP cases, while subsequent LA constituted 35.5% (478) of RI and 25.5% (1151) of GP cases. The average age-adjusted LA rate was 153.9 ± 17.3 per 100,000 in the RI cohort and 31.1 ± 2.3 per 100,000 in the GP cohort. Overall and primary LA rates for the GP Group declined 0.7% and 1.0%, while subsequent LA increased 0.1%. An increased LA rate for all categories (overall 4.9%, primary 5.1%, and subsequent 4.6%) was identified in the RI group. Overall, minor and major LA increased by 6.2% and 3.3%, respectively, in the RI group compared to a 0.8% rise in minor LA and a 6.3% decline in major LA in the GP group. RI females and males were 1.98-1.66 times higher risk of LA than their GP counterparts likewise, RI aged 0-49 years and 50+ years were 2.04-5.33 times higher risk of LA than their GP cohort. Diabetes mellitus (DM) was the most prevalent amputation predisposing factor in both groups with 81.5% of RI and 54.1% of GP diagnosed with DM. Also, the highest proportion of LA was found in the lowest income quintile for both groups (68.7% for RI and 45.3% for GP). Conclusion Saskatchewan's indigenous individuals, specifically First Nations persons registered under the Indian Act of Canada, experience LA at a higher rate than the general population. This disparity exists for all variables examined, including overall, primary, and subsequent LA rates, level of amputation, sex, and age. Amplification of the disparities will continue if the rates of change maintain their current trajectories. These results underscore the need for a better understanding of underlying causes to develop a targeted intervention in these groups.